The Middle Stone Age fauna from Olieboomspoort: an archaeozoological perspective - Nyambiya, Humphrey (Department of Archaeology, 2023)
Olieboomspoort is an archaeological site, which has evidence of human occupation going back possibly to the Earlier Stone Age, but more substantially to the Middle and the Later Stone Age. This site is located in the Waterberg Mountains of Limpopo Province, within the South African Savanna Biome. Archaeological excavations at this site began with the late Revil Mason in 1954, who attributed lithics from the Middle Stone Age deposits to the Pietersburg Industry. Mason did not mention any faunal remains from these Middle Stone Age layers. The site was later investigated by Maria van der Ryst, who excavated the Later Stone Age layers. In 2018, a new project led by Aurore Val and colleagues from the University of the Witwatersrand started at the site. This study focuses on the faunal material excavated in 2018 and 2019 from the Middle Stone Age layers. In southern Africa, Middle Stone Age archaeological research and, consequently, archaeozoological research, is concentrated on coastal and near coastal sites. While the research from these coastal and near coastal sites is insightful, little is known for the interior of southern Africa. The current study forms part of a series of renewed research at inland archaeological sites, aimed at aiding our understanding of the diversity of Middle Stone Age societies. This work presents the first taphonomic and archaeozoological analyses of the Middle Stone Age fauna from Olieboomspoort. A total of 1296 specimens were analysed. These include specimens that were plotted during excavations and those retrieved from the sieving refuse. This study identified the following species Alcelaphus sp., Oreotragus oreotragus, Raphicerus campestris, Raphicerus sp., Redunca sp., Sylvicapra grimmia, Syncerus caffer, Tragelaphus oryx, Equus sp., Proteles cristata, Felis silvestris, Papio sp., Lepus sp., snakes and tortoises. Thus, the faunal assemblage is taxonomically relatively diverse with 16 species identified. Bovids are the most represented and there is an abundance of small bovids. The presence of the extinct equid Equus capensis is suspected. Two species of carnivores, aardwolf (Proteles cristata) and African wild cat (Felis silvestris) were also identified. The taphonomic signatures of the faunal assemblage are indicative of several biotic modifiersincluding invertebrates. There is limited evidence for carnivore and porcupine action. Evidence of human modification is low and attested by only six pieces with cut-marks. This study identified the role of water, which likely transported some faunal material, and could have led to recovery biases. The taxonomic composition of the faunal assemblage provides a window onto the palaeohabitats present at the site. Several taxa, including the steenbok (Raphicerus campestris) and Equus sp. prefer open habitats. The identification of species that are water-dependent such as the buffalo (Syncerus caffer), and one species of reedbuck (Redunca sp), is suggestive of the presence of a nearby water source. This is consistent with the proximity of the Riet Spruit, which at present is a small river running a few meters below the site. Finally, the identification of baboons, leporids and klipspringers (Oreotragus oreotragus), animals which thrive in rocky areas, underpins the rocky morphology of the site's locality. Recent dating of two fossil bones from the Olieboomspoort Middle Stone Age layers by Val et al. (2021) gives a range of 150 kya, which places those layers within the Marine Isotope Stage (MIS) 6. MIS 6 was a glacial phase, which exact palaeoclimatic and palaeoenvironmental characteristics are still poorly understood for southern Africa, where there are also few dated archaeological sites from that period. Thus, we know relatively little about the subsistence strategies of MIS 6 human groups. In light of the above data, the current study adds some information about MIS 6 human subsistence strategies within the Savanna Biome.